The Impact of the Digital Al-Qur'an Thematic Learning Model on the Learning Achievement of Santri at Islamic Boarding Schools in Bandung Regency - Syamsul Hidayat; Amirsyah Amirsyah; Lukman Affandi; Munawar Rahmat (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aimed to determine the effect of the thematic digital al-Qur'an learning model on students' academic achievement in Bandung Regency boarding schools. The method used was a qualitative research method with a field research type. The research location was in one of the boarding schools in Bandung Regency, and the participants in this study were students. This study concluded that using the digital al-Qur'an in religious subjects can positively impact critical thinking skills, understanding, and memory. Using the versions of the Quran can also help students improve their memory. This is because features such as bookmarks, notes, and text highlighting provided by the digital Quran application can make it easier to revise and refer back to materials that have been previously learned. However, further research is needed to confirm these findings, specifically in the context of students.